Serum γ-glutamyl transpeptidase activity in liver disease. Issue 9 (September 1972) - Whitfield, J. B.; Pounder, R. E.; Neale, G.; Moss, D. W.
Abstract : Serum γ-glutamyl transpeptidase (GGT) activity correlates closely with the activities of alkaline phosphatase (ALP) and 5′-nucleotidase (5NT) in various forms of liver disease. Maximum elevations of all three enzyme activities are observed in diseases which particularly affect the biliary tract. Compared with the other two enzymes GGT is generally increased to a greater extent and is thus the most sensitive indicator of biliary-tract disease, while estimations of serum GGT are more reproducible than those of 5NT. However, a group of patients who had been treated with phenytoin and barbiturates were found to have elevated serum GGT activities without any other evidence of liver disease. The apparent effect of certain drugs on serum GGT activity indicates the need for caution in interpreting the results of this test.